Decoupling control with ETF based GPM tuning for multivariable processes - Khandelwal, Shubham; Aldhandi, Suresh; Detroja, Ketan P. (2019 Fifth Indian Control Conference (ICC), 2019)
Controlling MIMO processes in the face of multivariable interactions is one of the most challenging problems in process industries. While the interactions on one hand limits the direct applicability of SISO control design techniques, the complicated effective open-loop transfer functions on the other hand poses challenges in the PI controller tuning. In this paper, simplified decoupling based control design methodology for decoupling control of MIMO processes is proposed. To facilitate the multi-loop control design, the effective transfer function model representation of the decoupled process is deployed in this work. Further, the gain and phase margin method, due to its simplicity and robustness, is adopted here to tune the PI controllers. The performance of the proposed method is verified by performing simulation studies on various benchmark multivariable systems. Further, the robustness of the proposed method to uncertainties in the plant model is checked by performing closed loop simulations subject to a plant-model mismatch of ±30%.